Needs Assessment and Tailored Training Pilot for Emergency Care Clinicians in the Prehospital Setting in Rwanda - Naz Karim; Jeanne D’Arc Nyinawankusi; Mikaela S. Belsky; Pascal Mugemangango; Zeta Mutabazi; Catalina Gonzalez Marques; Angela Y. Zhang; Janette Baird; Jean Marie Uwitonze; Adam C. Levine (Western Journal of Emergency Medicine)
Background: In low- and middle-income countries (LMIC), 45% of deaths could be addressed by implementation of an emergency medical services (EMS) system. Prehospital care is a critical component of EMS worldwide, and basic, affordable training has been shown to improve EMS systems. However, patient outcome impact is unclear. In this study we aimed to assess the current state of prehospital care in Kigali, Rwanda, through a needs assessment, focused training intervention, and analysis of current practices and patient outcomes. Methods: We identified 30 clinicians through the prehospital medical command office and included them in the study. A prospective, nonrandomized, interrupted time-series approach was used. Data collected through closed- and open-ended questionnaires included age, sex, training, and knowledge assessment. We used the data to create a tailored, 18-hour training after which immediate and 11-month post-tests were administered. Linked prehospital and hospital care datasets allowed for evaluation of patient outcomes and prehospital process indicators that included training skill application, airway intervention, intravenous fluid administration, and glucose administration. Results: Of 30 clinicians, 18 (60%) were female, 19 were nurses, and 11 were nurse anaesthetists. Median age was 36, and median years providing care was 10 (IQR 7–11). Twenty-four (80%) participants completed immediate and post-test assessments. Mean knowledge across 12 core skills significantly improved from a pre-test mean of 59.7% (95% confidence interval [CI] 42.2–77.20) to a post-test mean of 87.8% (95% CI 74.7–100). At 11 months post-training, the score improvement maintained, with a mean score of 77.6% (95% CI 59.2–96.8). For patient outcomes, the total sample size was 572 patients; 324 of these patients were transported to the ED during the pre-training period (56.4%), while 248 were transported post-training. Prehospital oxygen administration for patients with a saturation level of <95% significantly increased pre- to post-training (66.7% to 71.7%; Δ = 5.0%; Δ95% CI 1.9,−8.1%). No significant changes were noted in patient treatment outcomes or other process indicators due to small sample sizes. Conclusion: This study provides insights on Rwandan EMS and demonstrates that a tailored intervention targeting education on prehospital process indicators has positive impacts on clinician knowledge and practice.